10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Despite widespread recognition of the need for training programs for healthcare professionals on intellectual disability, it remains inconsistently integrated into medical and nursing curricula. This systematic review aims to explore how training programs addressing care for adults with intellectual disabilities are designed and evaluated to promote inclusive healthcare. A total of 19 studies published between 2007 and 2026 were included, mainly mixed-methods and quantitative pre-post intervention studies. Findings highlight a predominance of interventions focusing on knowledge, skills, and attitudes, while also identifying two additional dimensions-affects and vocation-as relevant yet underexplored. A key issue identified is the mismatch between targeted learning outcomes and the variables assessed, along with the limited use of validated evaluation tools. Results also suggest that direct interaction with adults with intellectual disabilities enhances learning outcomes. The study concludes with recommendations to improve the theoretical grounding, methodological rigor, and inclusiveness of future training programs.